Implementasi Sistem Keterwakilan Perempuan dalam Pemilu: Studi pada Masyarakat Patrilineal di Indonesia - Bagus Anwar Hidayatulloh (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2014)
First regulation implementing quota policies 30% representation of women in thecomposition of the list of legislative candidates occurred in 2004. And until now therules are applied in the Act thereafter. Many areas of customary law in the country ofIndonesia implement patrilineal kinship system, which prioritizes family relationshipspaternal line, the position is more important than the position of the husband and wife.In asabah marriage act more as a guardian of marriage, marriage with an honestsystem, always follow the shelter's wife her husband. In the parental authority, thepower of the father (husband) take precedence over the power of women (wives) ofchildren in family relationships. Included in being a leader and representative of thepeople.